Household air pollution and childhood stunting in China: A prospective cohort study - Yao, Min; Li, Lingou; Yang, Mei; Wu, Yuanyuan; Cheng, Feifei (Frontiers in Public Health, 2022)
Background Exposure to air pollution, especially indoor air pollution, was associated with an increased risk of childhood stunting. However, few longitudinal studies have explored the long-term impacts of indoor air pollution from household solid fuel use on child growth. We aimed to investigate the association between household air pollution (HAP) from solid fuel use and childhood stunting in Chinese children. Method The longitudinal data from the Chinese Family Panel Study over 2010–2018 were included in this study with a total of 6,013 children aged 0–15 years enrolled at baseline. Exposure to HAP was measured as solid fuel use for cooking, while solid fuel was defined as coal and firewood/straw according to the questionnaire survey. Stunting was defined as−2SD below the height-for-age z-score (HAZ) of the reference children. Logistic regression and Cox proportional hazards models with time-varying exposures were employed to estimate the association between childhood stunting and HAP exposure. Results At baseline, children with exposure to HAP from combusting solid fuels had a relatively higher risk of stunting [OR (95%CI): 1.42 (1.24–1.63)]. Among children without stunning at baseline, those living in households with solid fuel use had a higher stunting risk over an 8-year follow-up [HR (95%CI): 2.05 (1.64–2.57)]. The risk of childhood stunting was increased for those with HAP exposure from firewood/straw combustion or with longer exposure duration [HR (95%CI): 2.21 (1.74–2.79) and 3.01 (2.23–4.08), respectively]. Meanwhile, this risk was significantly decreased among children from households switching from solid fuels to clean fuels [HR (95%CI): 0.53 (0.39–0.70)]. Solid fuel use was suggested to be a mediator of the relationship between poor socioeconomic factors (i.e., household income and parental education level) and childhood stunning, with a mediation effect ranging from 11.25 to 14.26%. Conclusions HAP exposure from solid fuel use was associated with childhood stunting. Poor parental education and low household income might be socioeconomic factors contributing to solid fuel use. Therefore, household energy policies to facilitate access to clean fuels are urgently needed, especially for low-income and low-educated households.